Two new species of Tomocerus ocreatus group with a single large distal dental spine (Collembola, Tomoceridae) - Gong, Xin; Qin, Chunyan; Yu, Daoyuan (Zootaxa, 2018)
Most members of Tomocerus ocreatus group have two distal large spines on dens, so far, only Tomocerus spinulus Chen & Christiansen, 1998 and Tomocerus leyensis Yu & Deharveng, 2018 have been described with only one distal large spine and are thus exceptional in this group. In the present paper, we report two other species with the same form. The two new species resemble T. spinulus in chaetotaxy, dental spine formula and general shape of the dental spines, but differ from it in several other characters, including position and shape of the prominent dorsal chaetae on the manubrium and dens. Also, T. pseudospinulus sp. nov. differs from T. spinulus in having larger denticles on the dental spines, and T. paraspinulus sp. nov. differs from T. spinulus in having longer antenna and more chaetae on the tenaculum. The two new species are similar, but can be distinguished by length of the antenna, number of the chaetae on tenaculum, status of the prominent manubrial dorsal chaetae and fine sculpture of the dental spines. Distances of COI mtDNA also support the validation of two new species. A key to species of T. ocreatus species-group with single large dental spine is provided.